Adsorption of Cd2+ from synthetic wastewater by modified leaves of Eupatorium adenophorum and Acer oblongum: thermodynamics, kinetics and equilibrium studies - Hemant Kumar Joshi; Mahesh Chandra Vishwakarma; Rajesh Kumar; Harish Sharma; Sushil Kumar Joshi; Narendra Singh Bhandari (Discover Water, 2022)
Abstract Heavy metals cause outrageous ecological risks when released into the environment from many point and non-point sources. Biosorbents prepared from the leaves of Eupatorium adenophorum (AEA) and Acer oblongum (AAO) were used as practical solutions to remove the toxic heavy metal cadmium (Cd2+) from wastewater. Biosorption of Cd2+ was investigated using AEA and AAO biomass under batch conditions. The effect of operating variables like temperature, contact time, the pH impact, and initial metal concentration and biosorbent portion on Cd2+ removal has been studied. The optimal pH and the sorbent dosage were found to be 7.0 and 2.0 g L−1, respectively, and removal efficiency attained was 93.3% with an equilibrium removal time of 90 min. The equilibrium uptake of Cd2+ was evaluated by Freundlich, Langmuir, and Temkin isotherm models. The Langmuir isotherm model was proved fit confirming single layer of sorption. The biosorption of Cd2+ onto activated AEA and AAO biomass achieved were 45.45 mg g−1 and 44.64 mg g−1 respectively. The adsorption affinity of AEA toward Cd2+ was discovered a lot more prominent than AAO biomass. The kinetic data of Cd2+ biosorption onto activated AEA and AAO, fitted with a pseudo-second-order well with higher values of R2 (> 0.99). Thermodynamics disclosed that the adsorption process was spontaneous (∆G0 < 0), endothermic (∆H0 > 0), and feasible (ΔS0 > 0). The adsorption of Cd2+ onto AEA was more exothermic and spontaneous than the AAO biosorbent. Additionally, FT-IR and SEM analysis uncovered that Cd2+ were adsorbed onto selected biomassdue to –NH–, –COOH, –OH, and –NH2 groups. Ionic, coordination bond formation, and electrostatic interaction with Cd2+ demonstrated that they were promising biosorbent for wastewater treatment.